Upregulation of heme oxygenase-1 protects genetically fat Zucker rat livers from ischemia/reperfusion injury - Amersi, Farin (American Society for Clinical Investigation, 1999)
We examined the effects of upregulation of heme oxygenase-1 (HO-1) in steatotic rat liver models of ex vivo cold ischemia/reperfusion (I/R) injury. In the model of ischemia/isolated perfusion, treatment of genetically obese Zucker rats with the HO-1 inducer cobalt protoporphyrin (CoPP) or with adenoviral HO-1 (Ad-HO-1) significantly improved portal venous blood flow, increased bile production, and decreased hepatocyte injury. Unlike in untreated rats or those pretreated with the HO-1 inhibitor zinc protoporphyrin (ZnPP), upregulation of HO-1 by Western blots correlated with amelioration of histologic features of I/R injury. Adjunctive infusion of ZnPP abrogated the beneficial effects of Ad-HO-1 gene transfer, documenting the direct involvement of HO-1 in protection against I/R injury. Following cold ischemia/isotransplantation, HO-1 overexpression extended animal survival from 40% in untreated controls to about 80% after CoPP or Ad-HO-1 therapy. This effect correlated with preserved hepatic architecture, improved liver function, and depressed infiltration by T cells and macrophages. Hence, CoPP- or gene therapy–induced HO-1 prevented I/R injury in steatotic rat livers. These findings provide the rationale for refined new treatments that should increase the supply of usable donor livers and ultimately improve the overall success of liver transplantation. J. Clin. Invest. 104:1631–1639 (1999).